Perayaan Grebeg Suro sebagai Potensi Pengembangan Sektor Wisata Budaya Ponorogo - Khoirurrosyidin, Khoirurrosyidin (ARISTO, 2018)
The celebration of â€œGrebeg Suroâ€ is an annual agenda organized by the Ponorogo Regency Government and is always present the attention and long-awaited of Ponorogo people (domiciled in the city of Ponorogo as well as in other cities) as well as various communities from other cities, including tourists from overseas. Ponorogo regency government has responded well by compiling various agenda of activities that can coloring the celebration of â€œGrebeg Suroâ€. Various events or competitions held in â€œGrebeg Suroâ€, starting various events or lombase not the opening ceremony of â€œGrebeg Suro of Grebeg Suro, Reyog Festival National Center of Peace in â€œAloon-Aloon Ponorogoâ€, Kirap Pusaka, Closing of â€œGrebeg Suroâ€, â€œLarung Risalahâ€, and various other events, it was able to attract a large audience or visitors. The celebration of â€œGrebeg Suroâ€ Â is actually derived from the customs of the community taken over by the Regional Government as the Annual Agenda by involving the community as a whole with a decision on the Head of Regent of Ponorogo Second Level Region No. 63 Juncto 130 Year 1987 about the Tourism Team of Ponorogo Level II Region.